First record of the tropical genus Rambutanura (Collembola: Neanuridae: Neanurinae) in Palearctic, with description of a new species from China - Dong, Ling; Yang, Yue-Li; Zhao, Yu-Yao; Wang, Yuan-Jun; Jiang, Ji-Gang (Zootaxa, 2018)
Genus Rambutanura Deharveng, 1988 of subfamily Neanurinae is herein recorded and a new species is described from China. A key to the species of the whole world of the genus is provided. In order to determine the new species, a new diagnosis within the genus Rambutanura Deharveng, 1988 is proposed. The new species is distinguished from all known members of the genus by its unique set of morphological characters notably: 2+2 depigmented eyes, mandible quadridentate, presence of 1 additional s-chaeta on each tubercle Di from Th. I to Abd. IV, presence of 2 additional s-chaetae on tubercle Dl from Abd. I to Abd. V, presence of guard chaetae sgd and sgv on AOIII, absence of digitate body tubercles.